2020
DOI: 10.1111/twec.13032
|View full text |Cite
|
Sign up to set email alerts
|

Regulatory barriers to trade in services: A new database and composite indices

Abstract: This paper presents new data on services trade regulation for 46 countries in 22 services sectors over 6 years (2014–2019). The data consist of qualitative information which is scored and weighted to produce composite indices. They cover market access and national treatment restrictions with respect to all GATS modes of supply, but also behind the border domestic regulation such as licensing, non‐transparent regulatory procedures and competition policy. The database is updated annually. The trade restrictivene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Studies have indicated that there is a robust negative relationship between the STRIs and services exports (Benz et al, 2020). This can be explained by the fact that STRIs capture barriers to competition, and the lack of foreign competition may reduce the incentives of local firms to innovate and expand beyond high-margin, local markets (Rouzet & Spinelli, 2016).…”
Section: The Importance Of Negotiations On Services Domestic Regul At...mentioning
confidence: 99%
“…Studies have indicated that there is a robust negative relationship between the STRIs and services exports (Benz et al, 2020). This can be explained by the fact that STRIs capture barriers to competition, and the lack of foreign competition may reduce the incentives of local firms to innovate and expand beyond high-margin, local markets (Rouzet & Spinelli, 2016).…”
Section: The Importance Of Negotiations On Services Domestic Regul At...mentioning
confidence: 99%
“…Regulatory barriers, including an absence of mutual recognition of qualifications, limit opportunities for services trade, as does lack of investment in human capital. While governments in developing Asia have progressively opened their economies through bilateral, regional, and multilateral trade agreements, these mostly focused on goods trade, and only later extended the commitments to services trade (Benz, Ferencz, and Nordas 2020). Sectors such as telecommunications or computer services, which underpin digital services trade, remain subject to restrictive regulatory regimes, and in many jurisdictions are becoming subject to stringent data localization requirements (Ferracane and van der Marel 2020; Ferencz 2019) and other barriers to data flows.…”
Section: Introductionmentioning
confidence: 99%
“…Evidently, the French exception had an effect: Only around 50% of admissions in France are for American film imports, compared to 60% to 90% in other European film markets (GreenAsh, 2017), period of observation not indicated]. Of course, this is not to deny the importance of barriers to trade in services, notably a host of regulations (see Benz et al, 2020) for a recent listing and evidence that they are related to the volume of trade]. However, these regulations may at least to some degree reflect citizens' desire to maintain a country's identity.…”
Section: Introductionmentioning
confidence: 99%